Theoretical Basis of Outsourcing - Kovalyov, A.V. (Економічний вісник Донбасу, 2013)
The present paper contains the analysis of the existing classifications of types of outsourcing. It demonstrates that these classifications are based on managerial and organizational criteria without taking into account the economical nature of outsourcing. Differences between outsourcing and purchase of products and services are described. A new approach to outsourcing is proposed that is based on economical aspects of this phenomenon. New classifications of types of outsourcing based on its economical nature and the types of interaction between companies are given. A list of methods of payment for outsourcing services is applied. У статті розглянуто існуючі класифікації видів аутсорсингу, доведено, що вони досліджують лише управлінську та організаційну складові аутсорсингу. Виявлено відмінності аутсорсингу від покупки товарів і послуг. Запропоновано підхід до аутсорсингу як до економічного феномену, побудовано класифікації видів аутсорсингу за економічним змістом і за способом організації взаємодії між підприємствами. Описано механізми взаємодії підприємств при аутсорсингу. В статье рассмотрены существующие классификации видов аутсорсинга, доказано, что они исследуют только управленческую и организационную составляющие аутсорсинга. Выявлены отличия аутсорсинга от покупки товаров и услуг. Предложен подход к аутсорсингу как к экономическому феномену, построены классификации видов аутсорсинга по экономическому содержанию и по способу организации взаимодействия между предприятиями. Описаны механизмы взаимодействия предприятий при аутсорсинге.